Sn Anodes Protected by Intermetallic FeSn2 Layers for Long‐lifespan Sodium‐ion Batteries with High Initial Coulombic Efficiency of 93.8 %. Issue 16 (10th March 2023) - Chen, Ming; Xiao, Ping; Yang, Ke; Dong, Boxu; Xu, Dong; Yan, Changyu; Liu, Xuejiao; Zai, Jiantao; Low, CheeTong John; Qian, Xuefeng
Abstract: With a theoretical capacity of 847 mAh g −1, Sn has emerged as promising anode material for sodium‐ion batteries (SIBs). However, enormous volume expansion and agglomeration of nano Sn lead to low Coulombic efficiency and poor cycling stability. Herein, an intermetallic FeSn2 layer is designed via thermal reduction of polymer‐Fe2 O3 coated hollow SnO2 spheres to construct a yolk‐shell structured Sn/FeSn2 @C. The FeSn2 layer can relieve internal stress, avoid the agglomeration of Sn to accelerate the Na + transport, and enable fast electronic conduction, which endows quick electrochemical dynamics and long‐term stability. As a result, the Sn/FeSn2 @C anode exhibits high initial Coulombic efficiency (ICE=93.8 %) and a high reversible capacity of 409 mAh g −1 at 1 A g −1 after 1500 cycles, corresponding to an 80 % capacity retention. In addition, NVP//Sn/FeSn2 @C sodium‐ion full cell shows outstanding cycle stability (capacity retaining rate of 89.7 % after 200 cycles at 1 C). Abstract : The intermetallic FeSn2 layer alleviates the huge volume change and prevents the coarsening of Sn anodes to provide a high ICE of 93.8 % and long life for sodium‐ion batteries.